2003
DOI: 10.1046/j.1365-246x.2003.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

A non-parametric hazard model to characterize the spatio-temporal occurrence of large earthquakes; an application to the Italian catalogue

Abstract: SUMMARY A new non‐parametric multivariate model is provided to characterize the spatio‐temporal distribution of large earthquakes. The method presents several advantages compared to other more traditional approaches. In particular, it allows straightforward testing of a variety of hypotheses, such as any kind of time dependence (i.e. seismic gap, cluster, and Poisson hypotheses). Moreover, it may account for tectonics/physics parameters that can potentially influence the spatio‐temporal variability, and tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 36 publications
2
78
1
5
Order By: Relevance
“…There is a unequivocal relationship between the hazard function and other statistics (i.e., the density function, the survivor function and the cumulative function), and it defines without ambiguity the time distribution of the point process. Moreover, its trend in time shows if the statistic indicates any kind of cycling behaviour (increasing trend), cluster behaviour (decreasing trend) or a random behaviour (constant trend), as already discussed in Sornette and Knopoff (1997) and Faenza et al (2003). So far, in geosciences, the stress release model (VereJones, 1987; and many other application of it) and the ETAS model (Ogata, 1988(Ogata, , 1998 are based on the study of the hazard rate function.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is a unequivocal relationship between the hazard function and other statistics (i.e., the density function, the survivor function and the cumulative function), and it defines without ambiguity the time distribution of the point process. Moreover, its trend in time shows if the statistic indicates any kind of cycling behaviour (increasing trend), cluster behaviour (decreasing trend) or a random behaviour (constant trend), as already discussed in Sornette and Knopoff (1997) and Faenza et al (2003). So far, in geosciences, the stress release model (VereJones, 1987; and many other application of it) and the ETAS model (Ogata, 1988(Ogata, , 1998 are based on the study of the hazard rate function.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent paper (Faenza et al, 2003), a non-parametric and multivariate method has been applied in order to estimate the spatio-temporal distribution of earthquakes in Italy . This method drastically reduces the a priori assumption on the temporal domain and allows to find a base-line hazard function, which trend versus time provides information on the earthquake generation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that the return period of major earthquakes must be searched and analyzed at the national/regional scale other than locally (i.e., for single faults or systems of connected faults). My analysis is someway related to previous works on the clustering of strong earthquakes in Italy (Faenza et al 2003(Faenza et al , 2004Lombardi and Marzocchi 2009). Those studies use much more complex statistical models that take into account both time and spatial characteristics of seismicity.…”
Section: Discussionmentioning
confidence: 84%
“…In a first approximation, SAs behave according to a Gutenberg-Richter (G-R) frequency distribution. The scientific community is equally divided about the implementation priorities of timedependent probability models (see, for example, the Straw Poll Results in Workshop 7 at http:// www.wgcep.org); characteristic earthquakes, seismic gaps, and quasiperiodicity models are alternative views to those statistical studies (e.g., Jackson 1991, 1999;Faenza et al 2003 for Italy), suggesting earthquake clustering in space and time. In these last studies, long-term forecasts are essentially an empirical description of observed spatial clustering; the temporal clustering is based on some completeness assumptions of having a record of observed events sufficient for statistical purposes.…”
Section: Individual Seismogenic Sources and Characteristic Earthquakementioning
confidence: 99%